Performance and health effects of Zuprevo 18% in newly received, highly stressed beef cattle - Schlegel, Ethan R.; Blasi, Dale A.; Hollenbeck, William R.; Oleen, Brandon E.; Renter, David G.; Spire, Mark F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
The objective of this study was to determine the health and performance effects of Zuprevo 18% (tildipirosin, 4 mg/kg body weight) during a 42-day backgrounding period when administered to high-risk transported cattle within 24 hours after arrival.
Keywords: Beef; Bovine respiratory disease; Zuprevo; Calves